Prevalence of depression among people who attempt suicide - G, Ramanujam; Rahuman, Abdul; Mahalakshmi, R. (International Journal of Research in Medical Sciences, 2017)
Background: This is a study aimed at assessing the prevalence of major depressive disorder among persons who attempted suicide. Methods: The study involved 30 persons above 18years of age of both sexes who has attempted suicide in the recent past. An informed consent was obtained from all of them. The prevalence of depression among those suicide attempters was studied based on major ICD- 10 depression inventory. Also, intent rating based on Beck’s suicide intent scale was done to assess the severity of suicide attempt. Questionnaire was given and the details were collected. Results: The prevalence of depression is estimated to be 20%. Regarding the suicidal intent, 13 cases (43.33%) showed high intent for suicide. Conclusions: Prevalence of depression is common among people who attempt suicide. Early diagnosis and intervention will reduce suicide attempts.